2017
DOI: 10.14202/vetworld.2017.1135-1138
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological features and pathological study of avian leukosis in turkeys' flocks

Abstract: Aim:The purpose of this study was focused on the identification of tumor diseases in turkeys on the basis of a detailed description of epidemiological features, clinical signs, lesions, and histopathological changes.Materials and Methods:Outbreak of a tumor disease in turkeys was investigated in various regions of Eastern Algeria. Four turkeys’ flocks aged from 17 weeks were affected, resulting to mortality often over 10%, on a period of 15 days. The main epidemiological characters, clinical signs, and lesions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Turkey cells are susceptible to ALV exogenous subgroups, although some show resistance to ALV-B, D, and J [121,137]. In 2017, Zeghdoudi et al [138] reported an outbreak of tumor disease in turkey flocks in Eastern Algeria, with a mortality rate of 10% in animals aged 17 weeks and older. Tumors tested positive to the ALV p27 (CA) antigen by ELISA.…”
Section: Alv Prevalence In Non-chicken Speciesmentioning
confidence: 99%
“…Turkey cells are susceptible to ALV exogenous subgroups, although some show resistance to ALV-B, D, and J [121,137]. In 2017, Zeghdoudi et al [138] reported an outbreak of tumor disease in turkey flocks in Eastern Algeria, with a mortality rate of 10% in animals aged 17 weeks and older. Tumors tested positive to the ALV p27 (CA) antigen by ELISA.…”
Section: Alv Prevalence In Non-chicken Speciesmentioning
confidence: 99%
“…Avian leukosis (AL) caused by ALV is a vertically-transmitted disease that results in severe immunosuppression, multiple organ retardation, atrophy, and tumours in chickens, and leads to a serious decline in performance and a large number of deaths [1]. ALV belongs to the genus Alpharetrovirus of the subfamily Orthoretrovirinae [12] and can be divided into seven subtypes, including ALV-A, ALV-B, ALV-C, ALV-D, ALV-E, ALV-J, and ALV-K. Clinically, three subtypes of ALV-A, ALV-B, and ALV-J are more commonly occurring in broilers, layers, breeders, and turkeys [13][14][15][16]. However, to date, no effective vaccine or specific drugs are available for the control of AL, except for the eradication of ALV to block its vertical transmission and spread in chicken flocks.…”
Section: Introductionmentioning
confidence: 99%